2018
DOI: 10.1007/978-3-030-03402-3_33
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Video Game Players’ Fun from Physiological and Behavioural Data

Abstract: Finding a physiological signature of a player's fun is a goal yet to be achieved in the field of adaptive gaming. The research presented in this paper tackles this issue by gathering physiological, behavioural and self-report data from over 200 participants who played off-the-shelf video games from the Assassin's Creed series within a minimally invasive laboratory environment. By leveraging machine learning techniques the prediction of the player's fun from its physiological and behavioural markers becomes a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Such measure offered greater objectivity but generally costly (temporally and financially) and challenging to interpret [39]. Furthermore, psychophysiological measures are primarily independent of bias and can be measured continuously without breaking flow [27]. Meanwhile, UX's subjective assessment revolves around interviews, focus groups, in-game probes, and questionnaires, which are low-cost alternatives with fewer challenges around interpretation and offer variable insights both in depths and focus.…”
Section: User Experiences and Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such measure offered greater objectivity but generally costly (temporally and financially) and challenging to interpret [39]. Furthermore, psychophysiological measures are primarily independent of bias and can be measured continuously without breaking flow [27]. Meanwhile, UX's subjective assessment revolves around interviews, focus groups, in-game probes, and questionnaires, which are low-cost alternatives with fewer challenges around interpretation and offer variable insights both in depths and focus.…”
Section: User Experiences and Behaviorsmentioning
confidence: 99%
“…Game and gaming can generally be defined as the activity and action of playing games, respectively. In recent years, video games had been increasingly linked with potential benefits from the perspective of social, cognitive, and motivational [27]. Although playing games for recreational purposes could promote relaxation, challenge, and socialization [89], unrestricted gaming may become counter-intuitive where vulnerable individuals could be exposed to pathological gaming behaviors [12] and ultimately be addicted [45].…”
Section: Introductionmentioning
confidence: 99%
“…For in-stance, the winning team of the IEEE CIG 2017 Game Data Mining Competition [16] used deep neural networks to predict the remaining lifetime of each player using real world data. In another example, machine learning models predict the churn rate, the expected expenses or the fun of the player to adapt the game experience [17,18].…”
Section: Quantity and Quality In Citizen Contributions To Citsci Proj...mentioning
confidence: 99%
“…Physiological measures and passive body/brain-computer interfaces offer tremendous possibilities for monitoring individual functional states. In recent years, several works have shown that physiological measures can be used to assess e.g., the operator functional state of workers (i.e., workload, stress, fatigue), videogame player fun level, or even health markers (Banaee et al, 2013 ; Gagnon et al, 2016 ; Harrivel et al, 2017 ; Fortin-Côté et al, 2018 ). Moreover, it has been demonstrated that such assessment can be leveraged to augment interactions with intelligent systems, such as adaptive videogames or adaptive workload management systems (Parnandi and Gutierrez-Osuna, 2015 ; Aricò et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%